2017
DOI: 10.1093/gbe/evx165
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Environment of cry1 Genes Indicates Their Common Origin

Abstract: Although in Bacillus thuringiensis the cry genes coding for the insecticidal crystal proteins are plasmid-borne and are usually associated with mobile genetic elements, several aspects related to their genomic organization, diversification, and transmission remain to be elucidated. Plasmids of B. thuringiensis and other members of the Bacillus cereus group (n = 364) deposited in GenBank were screened for the presence of cry1 genes, and their genetic environment was analyzed using a comparative bioinformatic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Because most entomotoxin genes are located within or adjacent to mobile entities (Fiedoruk et al . 2017 ) and because B. thuringiensis sv. israelensis strains carry numerous extrachromosomal molecules, they will always be able to adapt and survive by overcoming environmental changes and difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Because most entomotoxin genes are located within or adjacent to mobile entities (Fiedoruk et al . 2017 ) and because B. thuringiensis sv. israelensis strains carry numerous extrachromosomal molecules, they will always be able to adapt and survive by overcoming environmental changes and difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Within this island, several different transposases were annotated, suggesting multiple transposition events and pointing this region as a putative insertion hotspot ( Figure 2 ). Interestingly, the HER1410 cry1Ba4 -containing island organization resembles that of other B. thuringiensis plasmids where a N-acetylmuramoyl-l-alanine amidase coding sequence (CDS), coding for a germination key enzyme, precedes the insecticidal gene ( Fiedoruk et al , 2017 ). When the HER1410 chromosomal cry1Ba4 -containing island was compared with other plasmidial cryBa1 -containing cassettes described in Fiedoruk et al (2017) , a similar genomic organization was observed ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the HER1410 cry1Ba4 -containing island organization resembles that of other B. thuringiensis plasmids where a N-acetylmuramoyl-l-alanine amidase coding sequence (CDS), coding for a germination key enzyme, precedes the insecticidal gene ( Fiedoruk et al , 2017 ). When the HER1410 chromosomal cry1Ba4 -containing island was compared with other plasmidial cryBa1 -containing cassettes described in Fiedoruk et al (2017) , a similar genomic organization was observed ( Figure 2 ). Also, as in cry1Ba -containing plasmids, the HER1410 island only posseses one pesticidal gene (not within a PAI) and it is not preceded by a K þ (Na þ )/H þ antiporter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations